The effects of various warming up intensities and durations during a short maximal anaerobic exercise - de Bruyn-Prevost, P.; Lefebvre, F. (European Journal of Applied Physiology, 1980)
There appears to be a further consideration when preparing for anaerobic events (e.g., sprint and power activities) that is not so crucial for endurance events. It was shown that a one-minute maximal sprint test on a bicycle ergometer was adversely affected by rest between any type of warm-up and the event and by an aerobic warm-up that was too intense (in their case 75% VO2max). Implication. The amount and intensity of endurance type work that is engaged in prior to intense short events needs to be low (that was shown by the researchers to benefit the performance) and of a sufficiently brief duration so as not to lead to any perception of endurance effort or fatigue in the athlete.